Effect Of Governace On Performanceof County Governments In Kenya - Wahinya, Grace Njeri (Advances in Social Sciences Research Journal, 2020)
This study’s purpose was to evaluate the effect of governance on performance of county governments in Kenya. The data collection instrument used was Questionnaire. The questionnaire collected primary data from seven counties in Kenya (Machakos, Kakamega, Murang’a, Kilifi, Migori, Nakuru and Nairobi) drawn from 47 county governments in Kenya. The researcher identified the best performing county from every region of the former eight provinces of the republic of Kenya. The study adopted correlational research design. The study adopted two tools of analysis namely: correlation and regression analysis. The correlation analysis portrayed the positive correlation between the predictor and the response variables. Regression analysis was used to explain the relationship between the predictor and response variables. To provide the strength of the relationship between the model and the response variable and determine its goodness fit, R-squared was used. F statistics was used to test the significance of the regression model. The findings articulated that governance significantly performance of county governance. From the findings, the study concludes that the county governments should enhance on further improvement in the area of governance in order to enhance the benefit of governance on performance of county governments.